1997
DOI: 10.3354/ame012263
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions between picophytoplankton and micro- and nanozooplankton in the western Arabian Sea during the NE monsoon 1993

Abstract: The grazing pressure of micro-and nanozooplankton on phytoplankton was estimated in serial dilution experiments in the northwestern Arabian Sea and its adjacent areas (the Somali Current, the Somali Basin, the Gulf of Aden and the southern Red Sea) during the NE monsoon 1992-1993.Microzooplankton grazing rates @) on total phytoplankton (analyzed as chl a ) were generally exceeded by phytoplankton growth rates (g = 0.2 to 1.19 d-l, mean 0.48 d-'; p = 0.52 to 1.12 d-', mean 0.72 d-'1, resulting in an average dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 40 publications
(55 reference statements)
13
72
1
2
Order By: Relevance
“…Lastly, cell cycle analysis and diel variations in abundances and sizes of PRO indicated that growth and grazing mortality rates increased in the patch to at least 1.0 d -1 . Although PRO were initially believed to be constrained by synchronous cell division to growth rates of no more than 0.7 d -1 in the equatorial Pacific (Vaulot et al 1995), these higher rates under favorable environmental conditions are consistent with recent results from the Arabian Sea (Reckermann & Veldhuis 1997.…”
Section: Dynamics Of the Ironex II Bloomsupporting
confidence: 78%
“…Lastly, cell cycle analysis and diel variations in abundances and sizes of PRO indicated that growth and grazing mortality rates increased in the patch to at least 1.0 d -1 . Although PRO were initially believed to be constrained by synchronous cell division to growth rates of no more than 0.7 d -1 in the equatorial Pacific (Vaulot et al 1995), these higher rates under favorable environmental conditions are consistent with recent results from the Arabian Sea (Reckermann & Veldhuis 1997.…”
Section: Dynamics Of the Ironex II Bloomsupporting
confidence: 78%
“…This would suggest that the grazers of phytoplankton in the large size category did occur in our incubation bottles; otherwise the grazing impact of the large particles would be small (growth rate of large size category would largely exceed grazing mortality). Previous studies using size-fractionated dilution experiments also F. H. Chang et al: Scaling of growth rate and mortality 5277 support our findings, as their grazing mortality estimates from the < 20 µm and < 200 µm fractions do not significantly differ (Lessard and Murrell, 1998;Reckermann and Veldhuis, 1997). However, given relatively scarce studies on sizespecific growth rate and grazing mortality, it is not clear how the technical issues of such bottle incubation could affect the size-specific level investigation.…”
Section: Difficulties In Testing the Mte In Natural Phytoplankton Asssupporting
confidence: 53%
“…This new approach overcomes the deficiency in traditional sizefractionated chlorophyll measurements (Calbet et al, 2001Calbet, 2008;Lessard and Murrell, 1998;Reckermann and Veldhuis, 1997), which cannot provide satisfactory size resolution. Combining the detailed size information acquired from the FlowCAM and dilution technique, we were able to measure the size-specific growth and mortality rate of microphytoplankton with high resolution ranging from 10 to 300 µm.…”
Section: Flowcam Analysismentioning
confidence: 99%
“…Populations in the ϩFe bottles had cell division rates of 1.4 d Ϫ1 , which is equal to two doublings per day and significantly higher than any growth rate previously recorded for Prochlorococcus in the equatorial Pacific. Division rates greater than one division per day that are either supported by a second round of division seen in the DNA histograms or calculated by the dilution technique (Landry et al 1995) have only been reported for the highly productive Arabian Sea (Reckermann and Veldhuis 1997;Liu et al 1998;Shalapyonok et al 1998). These results indicate that the maximum cell division rate of Prochlorococcus in the equatorial Pacific if iron is abundant is 1.4 d Ϫ1 , significantly higher than the cell division rates found in situ in this and other studies (DuRand 1995;Vaulot et al 1995;Binder et al 1996;Latasa et al 1997;Liu et al 1997).…”
Section: Resultsmentioning
confidence: 99%